Liraglutide for idiopathic intracranial hypertension: a real‐world propensity score‐matched study - Ahmed Y. Azzam (14267391) (2025)
Objective Idiopathic intracranial hypertension (IIH) is a neurological disorder predominantly affecting young women with obesity, characterized by elevated intracranial pressure. While current treatments include weight loss counseling, medical therapies, and surgical interventions, their limitations necessitate exploring novel therapeutic approaches. We investigated the efficacy of liraglutide as an adjunctive therapy in IIH management. Methods We conducted a retrospective cohort study, analyzing adult patients with IIH. Through propensity score matching, we compared patients receiving liraglutide alongside standard therapy (n = 204) with those receiving standard therapy alone (n = 204). Primary outcomes included papilledema, headache manifestations, and visual disturbances, assessed at 3, 6, 12, and 24 months posttreatment initiation. Results Our matched cohorts were predominantly female (95.1% vs. 97.1%) with comparable mean ages (37.6 vs. 37.3 years). Liraglutide treatment demonstrated significant reduction in papilledema risk at 3 months (RR 0.333, 95% CI 0.167–0.664, p = 0.001), with sustained benefits throughout 24 months (RR 0.524, 95% CI 0.325–0.845, p = 0.006). While improvements were observed in visual disturbances, headache symptoms, and refractory IIH cases, these did not reach statistical significance. Interpretation Our findings suggest that liraglutide as an adjunctive therapy significantly improves papilledema outcomes in IIH patients, with the greatest effect observed at 3 months and sustained benefits over 2 years. This study provides promising evidence for liraglutide's role in IIH management, particularly in addressing papilledema. Other Information Published in: Annals of Clinical and Translational Neurology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/acn3.52300